2019
DOI: 10.2147/cia.s203658
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of transcutaneous electrical nerve stimulation (TENS) on acute postoperative pain intensity and mobility after hip fracture: A double-blinded, randomized trial</p>

Abstract: BackgroundTranscutaneous electrical nerve stimulation (TENS) is a noninvasive modality which may be used to reduce acute postoperative pain. Intense perioperative pain within the first few days after hip fracture surgery is common and is related to negative consequences such as restricted and delayed ambulation.ObjectiveThe objective of the present study was to examine the effect of incorporating TENS treatment on pain intensity, and mobility, with standard rehabilitation care during the acute post-operative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 40 publications
1
44
0
3
Order By: Relevance
“…Postoperative TENS has been proposed to minimize the need for opioid and nonopioid analgesics (5) in many types of procedures (6–12). The efficacy of TENS demonstrated in this meta‐analysis support the findings of Sbruzzi et al and reinforces the benefits of TENS in postoperative care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative TENS has been proposed to minimize the need for opioid and nonopioid analgesics (5) in many types of procedures (6–12). The efficacy of TENS demonstrated in this meta‐analysis support the findings of Sbruzzi et al and reinforces the benefits of TENS in postoperative care.…”
Section: Discussionmentioning
confidence: 99%
“…TENS can be used as an effective adjunct for managing postsurgical pain and to minimize the need for opioid and nonopioid analgesics as part of a multimodal approach to pain (5). TENS has been shown to be effective in noncardiothoracic procedures, and has been implemented following abdominal, hip, knee and shoulder surgeries, amputations, and oocyte retrievals (6–12). Excessive use of narcotics to control pain following such procedures can lead to side effects such as respiratory depression, sedation, nausea, vomiting, and pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…Additional improvements in the active TENS group were a greater increase in walking distance on the fifth postoperative day and a higher level of mobility compared to the sham TENS group. The authors concluded that adding TENS to the standard care of elderly patients in the early postoperative period following surgical fixation of extracapsular hip fracture with a Gamma nail could be recommended for pain management during walking and functional gait recovery [ 126 ].…”
Section: Perioperative Carementioning
confidence: 99%
“…Additional improvements in the active TENS group were a greater increase in walking distance on the fifth postoperative day and a higher level of mobility compared to the sham TENS group. The authors concluded that adding TENS to the standard care of elderly patients in the early postoperative period following surgical fixation of extracapsular hip fracture with a Gamma nail could be recommended for pain management during walking and functional gait recovery [125].…”
Section: Pain Was Measured With the Western Ontario And Mcmaster Univmentioning
confidence: 99%